Phase II clinical trial of neoadjuvant trabectedin in patients with advanced localized myxoid liposarcoma - Gronchi, Alessandro; Bonvalot, Sylvie; Hohenberger, Peter (Annals of oncology, 2012)
Abstract Background: To evaluate neoadjuvant trabectedin (1.5 mg/m2 24-h i.v. infusion every 3 weeks; three to six cycles) in patients with locally advanced my